MARKETING EFFICIENCY ANALYSIS OF YAM VALUE CHAIN IN THE NORTHERN REGION OF GHANA - Iddi, F. Y.; Donkoh, S. A.; Danso-Abbeam, G.; Karg, H.; Akoto-Danso, E. K. (UDS International Journal of Development, 2018)
For smallholder households, yam production constitutes an important source of food and income and also plays a vital role in their socio-cultural lives. This paper sought to evaluate the marketing efficiency of key players of the value chain as well as investigate their challenges. The study used cross-sectional data of 400 key players sampled through a multi-stage technique. Gross margin and marketing efficiency analyses were employed for the computation, while the Kendall Coefficient of Concordance was used for constraint analysis. The study revealed that an average yam value chain player makes relatively good margins with an average net margin of GH¢93.05, GH¢167.63, GH¢73.80 per 100 tubers for farmers, wholesalers and retailers respectively. The marketing efficiency of the farmers, retailers, and wholesalers was estimated to be 251%, 213% and 44%, respectively. Also, the players ranked erratic rainfall pattern, poor transportation system, high deterioration rate of yam, price fluctuation, among others as the most pressing problems hindering the smooth operation of the yam value chain. The yam value chain can be stepped-up by the provision of affordable storage facilities, development of the road network as well as organizing business and financial management training for actors. Keywords: Constraints, Gross Margin, Market Efficiency, Yam, Northern Ghana